Early Transcriptional Signature in Dendritic Cells and the Induction of Protective T Cell Responses Upon Immunization With VLPs Containing TLR Ligands—A Role for CCL2 - Gomes, Ariane C.; Mohsen, Mona O.; Mueller, Julius E.; Leoratti, Fabiana M. S.; Cabral-Miranda, Gustavo; Bachmann, Martin F. (Frontiers in Immunology, 2019)
Inducing T cell responses by therapeutic vaccination requires appropriate activation of antigen presenting cells (APCs). The use of virus-like particles (VLPs) containing Toll-like receptor (TLR) ligands has demonstrated remarkable potential in activating APCs and modulating the immune response both for prophylactic vaccines as well as immunotherapy. Here, we employed VLPs associated to TLR ligands as tools to modulate cytotoxic response mediated by CD8+ T cells and provide further insight in the development of T cell-based immunotherapy. We have investigated the in vivo transcriptional signature in dendritic cells (DCs) from mice immunised with VLPs containing distinct classes of nucleic acid and correlated the expression patterns with the efficiency of induced T cell responses. We identified key pathways activated in DCs that are involved in the appropriated induction of T cell responses and show evidence for the modulatory effect of CCL2 in CD8+ T cells responses. These insights shed light on immune networks that are pivotal for the induction of potent cytotoxic T cell responses and identify key genes for appropriate DC activation and subsequent modulation of the adaptive immune response.